Incidence of rheumatic fever and rheumatic heart disease and its associated factors among paediatric patients in Malaysia - Nik, Mohd Anas Che (2023)
Acute rheumatic fever (ARF) cases are still a significant cause of morbidity and early death in poor and developing countries. In Malaysia, ARF remains the primary cause of acquired cardiac problems, particularly in the East Coast of Peninsular Malaysia and East Malaysia. This study aims to reveal the incidence of ARF and its risk factors to develop better strategies to combat ARF in Malaysia. Methodology: This cross-sectional study was conducted across 23 centres in Malaysia over a period of one year from July 2021 to June 2022. The study included all new cases of ARF or RHD with a ratio of one case to two control patients. Sociodemographic characteristics such as age, gender, race, parental education, house condition, and monthly income were recorded. Clinical profiles such as clinical presentation, echocardiography findings, complication, management and outcome of the disease were captured. Multivariate analyses were used to determine the associated sociodemographic risk factors. Result: The incidence of ARF was 34.1 per 100,000 paediatric admissions, with Kelantan and Sabah states recording most of the cases. The most common clinical presentation for ARF patients was carditis (85.7%) and migrating polyarthritis (31.4%), with majority had valve involvement and mitral regurgitation being the most common valvular abnormality. Multivariate analysis showed age, total monthly income and rural population are significant risk factors for ARF. Conclusion: This study showed that the incidence of the Acute Rheumatic Fever was still high in Malaysia. Factors such as age, low socioeconomic status and rural residential area showed strong correlation of getting the ARF.